RESEARCH OF DEGRADATION OF THE KALUSHSKYS LAND RESOURCES IN THE REGION OF THE IVANO-FRANKOVSK WITH USE OF GEOINFORMATION TECHNOLOGIES - Дудар, Т.; Станкевич, С.; Лоїк, І.; Мартинова, О. (Science-based technologies, 2012)
The analysis of main causes of land degradation in Kalush district of Ivano-Frankivsk oblast is given in this pub-lication. Vegetation cover and soil erosion dynamics were highlighted as the main indicators of land degradation. The land degradation map for the researched area was built using multispectral space images as well as digital terrain model, soil and climatic characteristics.